Severely Calcified True Aneurysm: A Thought-Provoking Case of Solitary Origin and Postoperative Management - Tani, Ryotaro (Am J Case Rep, 2019)
Patient: Male, 70 Final Diagnosis: Splenic artery aneurysm Symptoms: Asymptomatic Medication: — Clinical Procedure: Surgery and Endoscopy Specialty: Surgery OBJECTIVE: Unknown ethiology BACKGROUND: Visceral arterial aneurysms are rare. Most splenic arterial aneurysms (SAAs) are saccular and are in the distal third of the splenic artery. Suggested major causes of SAAs are atherosclerosis, pregnancy, and inflammation. We report the case of a patient who with a SAA extending almost the full length of his splenic artery. CASE REPORT: A solitary true aneurysm that extended almost the entire length of the splenic artery was incidentally detected in an asymptomatic 70-year-old male patient with a history of myasthenia gravis and diabetes mellitus. His SAA was severely calcified, but other arteries showed no calcification. The aneurysm had been slightly enlarged toward the celiac artery for 2 years, and aneurysmectomy and splenectomy were performed. Vascular clips were carefully placed at the intact splenic artery without disturbing arterial flows from the celiac artery. Arterial branch from the SAA was ligated at an intact area, and the pancreatic capsule was densely adherent with the calcified aneurysm wall. The pancreas was preserved, although the pancreatic parenchyma was widely exposed during aneurysmectomy. Pathological examination revealed no atherosclerotic changes. Postoperatively, a pancreatic fistula developed, which was treated by placing an intraperitoneal drain and retrograde pancreatic drainage tube. Nevertheless, the intractable pancreatic fistula triggered a bacteriogenic infection, resulting in intraperitoneal abscess. Continuous local lavage via transnasal continuous infusion and endoscopic transgastric drainage was performed, until the fistula closed. He was healthy at 9 months after surgery. CONCLUSIONS: A SAA that had the rare form and solitary origin was treated. Continuous local lavage has a therapeutic potential for a pancreatic juice-related bacteriogenic complication.